Social Factors Acting as a Catalyst for the Drug Abuse: A Case of District Kech Balochistan (Medical Forum Monthly, 2022)
Objective: This study aims to determine the factors affecting entry into drug abuse in the District Kech of Balochistan.Study Design: Cross-Sectional studyPlace and Duration of Study: This study was conducted at the District Kech of Balochistan from April to June 2022.Materials and Methods: Data were collected from 285 drug-addicted people. Partial Least Square Structural Equation Modelling was used to analyze the data.Results: The findings of this study shows that access to drugs, family background, parental control, peer group influence, and unemployment have a key role in the entry into drug abuse for the drug adductors of the district Kech Balochistan. While Family cohesion, street gangsters, and stress have no significant role.Conclusion: From the findings of this study, it is concluded that access to drugs, family background, parental control, peer group influence, and unemployment should be controlled to avoid more drug addiction in district Kech of Balochistan.